Оцінка ефективності використання методів штучного інтелекту для аналізу фінансових звітів та прогнозування динаміки акцій - Границя, А. В. (ХНУРЕ, 2024)
This research investigates artificial intelligence techniques for forecasting stock market trends through corporate report analysis. It emphasizes the utilization of neural networks and machine learning algorithms, particularly focusing on natural language processing (NLP) and recurrent neural networks, for sentiment analysis and trend prediction. The study aims to enhance investment strategies by improving the accuracy and speed of market change forecasts, demonstrating AI's significant potential in financial analysis and decision-making processes.
Keywords: BERT; штучний інтелект; фінансовий звіт; динаміка акцій